PENGARUH INFLASI, LOAN TO DEPOSIT RATIO DAN PERTUMBUHAN EKONOMI TERHADAP NON PERFORMING LOAN PADA BPR SUMATERA BARAT - Nurmi Siringo; Ali Anis; Ariusni Ariusni (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2015)
This study aims to determine the effect of inflation, Loan To Deposit Ratio, and economic growth of the Non-Performing Loan in Rural Bank of West Sumatra.The type of data in this research is secondary data that is both quantitative and Time Series Data from the years 2005-2013. Data were analyzed with regression methods and estimation OLS (Ordinary Least Square).The results showed that: (1) inflation is not a significant negative effect on the Bank's Non-Performing Loan Rural West Sumatera (2) Loan To Deposit Ratio was not significant positive effect on Non-Performing Loans in the Bank Rural West Sumatera  (3) economic growth significant negative effect on Non-Performing Loans in the Rural Bank of West Sumatra, (4) inflation, Loan To Deposit Ratio and economic growth together significant effect on Non-Performing Loans in the Rural Bank of WestKeywords : Inflation, Loan To Deposit Ratio, economic growth.